The Principal's Performance as a Supervisor in Improving Teacher Professionalism - Madarina Abidin; Nurdyansyah Nurdyansyah; Hidayatulloh Hidayatulloh (International Consortium of Education and Culture Research Studies, 2020)
This aim of this study is to analyze and describe how the principal's performance as a supervisor in improving teacher professionalism. Begin from the supervision plan, implementation of supervision, and follow-up and evaluation carried out by the principal. This study used qualitative as the method of this research, data collection techniques used are observation, interviews, and documentation. The study was conducted at SDN Wadungasih 2. Research subjects included principals and teachers. Analysis is done by reducing data. The results of the study show that: (1) The Supervision, which is carried out by the principal is only done once a year, (2) The Supervision begins with the plan of the form of making programs that have been prepared at the beginning of the semester (3) The Supervision is divided into two stages namely, administrative supervision and supervision at the time of learning activities no follow-up is given after the supervision ends.